Urban Spaces and Architecturally Defined Identity in Nathanael West’s Miss Lonelyhearts - Wayne E. Arnold (European Journal of American Studies)
Nathanael West’s 1933 novella, Miss Lonelyhearts, depicts a New York City that defines its inhabitants through the architectural structures enveloping them. Throughout West’s narration, spaces and places within the city become social critiques, as these locations represent what Henri Lefebvre describes as abstract spaces: various spaces that are multifaceted in their functions due to their shifting—and abstract—relation with a larger environment. Fusing an analysis of space and the individual serves as a springboard for reexamining West’s novella of place and space in the then modern metropolis of the 1920s. Locales within the narrative illustrate how modern public and private spaces detrimentally precipitate the psychological downward spiral of the protagonist. This article argues that by scrutinizing the physical setting in the narrative we will illuminate a new understanding of the repressed, agoraphobic identity of the protagonist, Miss Lonelyhearts, and bring a fresh phenomenological interpretation to the demise of one of West’s most complicated characters.